A Brief Discussion on Gesture Controlled Robot - Chattopadhyay, Adriza; Mukherjee, Belonia; Pal, Arnab; Chakraborty, Debraj (International Journal of Computer Sciences and Engineering, 2025)
The model discussed here is a gesture controlled robot having two wheels on either side just like a car. The key features described in the model are i) controlling the movement of the wheels using an embedded system ii) using the concept of image processing hand gestures are analyzed and according to the gestures the robot moves.[1]The embedded system used here is an Arduino Uno board. It is a microcontroller[9](Atmega328) based The PYTHON program and the Arduino program are merged using Serial import interface. board having 14 digital pins (out of which some are PWM pins) and 6 analog pins. The Arduino have been programmed using JAVA. Two driving motors have been connected with each of the wheels and hence a motor driving circuit (IC no. L239D) has been used. The gesture detection part has been done using PYTHON programming.